Land subsidence and rebound response to groundwater recovery in the Beijing Plain: A new hydrological perspective - Dexin Meng; Beibei Chen; Huili Gong; Shubo Zhang; Rui Ma; Chaofan Zhou; Kunchao Lei; Lewei Xu; Xincheng Wang (Journal of Hydrology: Regional Studies)
Study region: Beijing Plain (BJP), China. Study focus: The rapid land subsidence in BJP has been alleviated since the South-to-North Water Diversion Project. Groundwater level (GWL) is recovering with more precipitation from climate change. The land deformation pattern is evolving into a coexistence of subsidence-rebound. Hence, Sentinel-1A and InSAR were used to investigate surface deformation in 2016–2022, and a new Transfer Function Analysis (TFA) framework was proposed by integrating deformation, precipitation, wells, and hydrogeological data. This study quantified the response characteristics among precipitation, GWL, and deformation according to TFA, aiming to explore the differential response mechanisms of subsidence-rebound to GWL affected by monsoon precipitation. The maximum rebound was estimated. New hydrological insights for the region: Compared to 2011–2015, the area with a subsidence rate of over 60 mm/yr in 2016–2022 has decreased by 37 %. Local areas have experienced a rebound, the area with a rebound rate of over 5 mm/yr is 67.2 km2. The seasonal response between precipitation and GWL exists throughout the plain, while the seasonal response between GWL and deformation is only consistent in the northwest. The aquifer schematic models suggest that the differential deformation response is related to lithology and residual deformation. In the southeast, the aquifer head is still below the adjacent aquitard head, with a larger residual deformation disturbing the seasonal response caused by precipitation. A longer delay between GWL recovery and surface rebound was observed in the aquifer with thicker clay layers, with over 77 % of the compaction being irreversible.